On the BET Surface Area of Nanocellulose Determined Using Volumetric, Gravimetric and Chromatographic Adsorption Methods - Kondor, Anett; Santmarti, Alba; Mautner, Andreas; Williams, Daryl; Bismarck, Alexander; Lee, Koon-Yang (Frontiers in Chemical Engineering, 2021)
Volumetric N2 adsorption at –196 °C is generally accepted as “gold standard” for estimating the Brunauer-Emmet-Teller (BET) surface area of nanocellulose. It is unclear however, whether the BET surface area of nanocellulose obtained at such low temperatures and pressures is meaningful at an absolute sense, as nanocellulose is used at ambient temperature and pressure. In this work, a systematic evaluation of the BET surface area of nanocellulose using a highly crystalline bacterial cellulose (BC) as model nanocellulose was undertaken to achieve a comprehensive understanding of the limitations of BET method for nanocellulose. BET surface area obtained using volumetric N2 adsorption at –196 °C was compared with the BET surface area acquired from gravimetric experiments using n-octane adsorption measured using dynamic vapour sorption (DVS) and n-octane adsorption determined by inverse gas chromatography (iGC), both at 25 °C. It was found that the BET surface area calculated from volumetric N2 adsorption data was 25% lower than that of n-octane adsorption at 25 °C obtained using DVS and iGC adsorption methods. These results supported the hypothesis that the BET surface area of nanocellulose is both a molecular scale (N2 vs n-octane, molecular cross section of 0.162 nm2 vs 0.646 nm2) and temperature (–196 °C vs 25 °C) dependent property. This study also demonstrates the importance of selecting appropriate BET pressure range based on established criteria and would suggest that the room temperature gravimetric measurement is more relevant for many nanocellulose applications.